Local Knowledge as a Strategy for Village Resilience in Hanjeli Tourism Village, Sukabumi, Indonesia - Mad Fadhol; Palupi Lindiasari Samputra (International Journal Labs, 2025)
Local knowledge plays a crucial role in strengthening village resilience amidst the challenges of modernization and environmental change. This study examines the contribution of local knowledge to village resilience through four main aspects: ecology, social, economic, and institutional, with a focus on Hanjeli Tourism Village, Sukabumi, Indonesia. Using a qualitative approach with in-depth interviews and literature review methods, this research analyzes how local practices support village sustainability. The findings indicate that in terms of ecology, hanjeli-based agricultural practices contribute to biodiversity conservation and sustainable natural resource management. From a social perspective, strong social capital and intergenerational knowledge transfer play a crucial role in preserving traditional practices. In the economic aspect, the diversification of hanjeli-based enterprises, including educational tourism and derivative products, enhances the community’s economic resilience. Meanwhile, the institutional aspect is reflected in the community’s role in resource management and the village’s recognition as part of the UNESCO Global Geopark. This study recommends policies that strengthen the documentation of local knowledge, enhance community participation in resource governance, and encourage the integration of traditional practices into sustainable village development strategies.